Longitudinal changes in participant and informant reports of subjective cognitive complaints are associated with dementia risk - Numbers, Katya; Lam, Ben C. P.; Crawford, John D.; Kochan, Nicole A.; Sachdev, Perminder S.; Brodaty, Henry (Frontiers in Aging Neuroscience, 2023)
Background Individuals with subjective cognitive complaints (SCCs) are at an increased risk of dementia. Questions remain about participant-reported versus informant-reported SCCs as indicators of future dementia and about longitudinal changes in participant-and informant-reported SCCs and risk of incident dementia. Method Participants were 873 older adults (M = 78.65-years; 55% female) and 849 informants from the Sydney Memory and Ageing Study. Comprehensive assessments occurred biennially, and clinical diagnoses were made by expert consensus for 10-years. SCCs were participants’ and informants’ responses to a single binary question concerning their/the participant’s memory decline (Yes/No) over the first 6-years. Categorical latent growth curve analyses, using the logit transformation, were used to model SCC change over time. Associations of initial propensity to report SCCs at baseline, and change in propensity to report SCCs over time, with dementia risk were examined using Cox regression. Results 70% of participants reported SCCs at baseline, with a proportional increase in the odds of reporting by 11% for each additional year in the study. In contrast, 22% of informants reported SCCs at baseline, with a proportional increase by 30% in the odds of reporting per year. Participants’ initial level of (p = 0.007), but not change in SCC reporting (p = 0.179), was associated with risk of dementia controlling for all covariates. Both informants’ initial level of (p < 0.001), and change in (p < 0.001), SCCs significantly predicted incident dementia. When modelled together, informants’ initial level of, and change in, SCCs were still independently associated with increased dementia risk (p’s < 0.001). Conclusion These data suggest that informants’ initial impressions, and increased reporting, of SCCs appear to be uniquely prognostic of future dementia compared to participants’, even based on a single SCC question.